The Impact of Madrasah Integration in the National Education System on the Academic Quality of Madrasah Aliyah Alumni in South Sulawesi - Aminullah, Aminullah; Mujahidin, Mujahidin; Syahabuddin, Syahabuddin; Salenda, Kasjim; Yussuf, Ahmad (Universitas Islam Negeri Mataram, 2024)
Madrasah has been integrated into the national education system. This policy pushed the reconstruction of the curriculum regarding the components of religious and general subjects and its implications for madrasah alums. This research aims to examine the impact of the Ministrial Joint Decree on the academic quality of madrasah aliyah alums in South Sulawesi. This qualitative research gathered the data through interviews with the madrasah principals, teachers, and the head of the education division at the Ministry of Religious Affairs of South Sulawesi. This study shows that both state and private Islamic senior high schools in the province applied various strategies to overcome curriculum overload through maximizing learning hours, improving the quality of teachers, and applying boarding school system where learning activities adopt a fullday system. Through such mechanism, that madrasahs produced competitive alums. A further implication for Islamic public and private schools' alums is concerned with the increase in the number of their alums in pursuing education at prominent state universities in Indonesia.